The Investment-Financing-Growth Nexus : The Case of Liberia - Clark JR, John.; Rosales Torres, Manuel (Washington, D.C. : International Monetary Fund, 2013)
Liberia is facing large infrastructure gaps and developmental needs that constrain the country's growth potential. The government has set an ambitious agenda to transform the economy and to reach middle-income country status by 2030 by scaling up investment in infrastructure and human capital. Fiscal space remains constrained by rigidities in current spending and the government will need to resort to borrowing to close some of the gaps. This paper presents an estimate of the nexus between public investment, financing, and growth in Liberia using an inter-temporal macroeconomic model. The model has been calibrated as much as possible to Liberian economic data and assumes that public investment has a high economic and social rate of return and is highly complementary toward private sector investment. The objective of the paper is to contribute to the debate on how fast public investment should be scaled up to address the country's developmental needs. The paper also highlights the trade-offs and potential risks associated with different financing options and the required changes in fiscal policy to ensure macroeconomic stability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet